IRREGULARITIES IN VOCABULARY LOAD AND DISTRIBUTION IN SAME LEVEL TEXTBOOKS WRITTEN BY DIFFERENT WRITERS - Jayakaran Mukundan (Universitas Katolik Indonesia Atma Jaya, 2007)
A syllabus provides a focus for what to be studied and how the contents should be selected and sequenced. In Malaysia, the syllabus has an additional role that is to guide the textbook writers in producing textbooks for school use. The English Language Programmes for Malaysian secondary schools provide more than one textbook for every academic level. These textbooks must comply with the syllabus in order to achieve the same learning objectives at the end of each programme. There will also be public examinations at the end of Form Three and Form Five. Two Form 2 textbooks were chosen and WordSmith 3.0 was used to analyse these textbooks to identify whether the textbooks were similar and had included all the contents listed in the syllabus. The findings show that one of the textbooks is relatively better that the other in terms of types, distribution of words, presentation of items in the syllabus and repetition of new linguistic items throughout the textbook. This reveals that ad hoc writing of textbooks by different writers for a similar level can lead to irregularities, the most severe problem being non-conformity to syllabus requirements.Keywords: distribution of words, presentation of items, repetition of new linguistics items, textbooks, Wordsmith 3.0, syllabus requirements